Characterization of a poly(butylene adipate-co-terephthalate) hydrolase from the aerobic mesophilic bacterium Bacillus pumilus. (March 2017) - Muroi, Fumihiro; Tachibana, Yuya; Soulenthone, Phouvilay; Yamamoto, Kiriko; Mizuno, Tsukasa; Sakurai, Takanori; Kobayashi, Yukiko; Kasuya, Ken-ichi
Abstract: The use of biodegradable plastic films made of poly(butylene adipate- co -terephthalate) (PBAT) to improve crop production has been proposed. Because the film after use is expected to be degraded on site, it is important to understand the biodegradation mechanism of PBAT in aerobic and mild temperature conditions. We therefore isolated three PBAT-degrading strains, NKCM3201, NKCM3202, and NKCM3101, from soil environments. Phylogenetic analysis revealed that the strains are closely related to Bacillus pumilus . Strain NKCM3201, which degraded PBAT film at the fastest rate (12.2 μg/day/cm 2 ) and grew well at 30 °C to 40 °C in aerobic conditions, was selected for further analysis. We cloned the 648-bp coding region of the PBAT hydrolase (PBATH Bp ) gene, which encodes a 215-amino acid protein containing a signal peptide of 34 residues. Mutation analyses revealed that PBATH Bp belongs to the serine hydrolase superfamily, with a catalytic triad composed of Ser77, Asp133, and His156. Homology 3D modeling of PBATH Bp using Bacillus subtilis 168 lipase as a template showed that the enzyme belongs to the α/β hydrolase fold family, which lack a lid domain on its surface. PBATH Bp hydrolyzed PBAT, poly(butylene succinate- co -adipate) (PBSA), poly(ethylene succinate) (PESu), and polycaprolactone (PCL) films at a degradation rate of 14.3, 3.3 × 10 2, 7.0 × 10 2, and 1.1 × 10 2  μg/cm 2 /day, respectively. Liquid chromatography-mass spectrometry analysis of degradation products from PBAT revealed that PBATH Bp hydrolyses ester bonds between butanediol and terephthalate (B-T bonds) at much slower rates than ester bonds between adipate and butanediol. This ester bond preference may explain the very slow PBAT degradation rate compared to PBSA, PESu, and PCL. This is the first report of a PBAT hydrolase from an aerobic mesophilic bacterium, and may contribute to our understanding of PBAT biodegradation under mild temperature conditions.